THE IMPLEMENTATION OF RECIPROCAL TEACHING LEARNING MODEL TO IMPROVE THE UNDERSTANDING OF PHYSIC CONCEPTS FOR OPTICAL MATERIAL IN CLASS X SMK - Nadya Hari Pratiwi; M. Rahmad; Fakhruddin Z; Kartika Lona (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
The still low understanding of the concept of students in vocational schools in learning physics, due to the lack of innovative learning, so it needs innovation such as a reciprocal teaching model that implements four independent understanding strategies, namely summarizing the material, compiling questions, explaining, and predicting. The purpose of this research was to determine the improve in understanding of students' concepts in the class applying the reciprocal teaching model with conventional classes at Vocational High School (SMK) Abdurrab Pekanbaru. The population in this research were 130 students spread over five classes and samples were taken by simple random sampling, so that 2 classes of samples were obtained with 52 students. The research instrument was in the form of concept comprehension test questions consisting of pretest and posttest. The Test  in the form of multiple choice reasoned with 4 choices totaling 15 items. The instruments are arranged according to the category of understanding the concepts of translation, interpretation, and extrapolation. Data collection techniques in the form of scores on the concept understanding results obtained from the pretest and posttest scores. The data is processed by descriptive analysis. The results showed that students of class X SMK Abdurrab Pekanbaru in optical material learning, had a difference in increased understanding of concepts. The average score of concept understanding after the implementation of learning in the experimental class was 82.44 with a high category, while the control class was 59.68 with a low category. To that end, the implementation of the reciprocal teaching learning model, is able to better enhance the understanding of physics concepts in optics learning for students in class X SMK Abdurab Pekanbaru.